Sustainable Tourism Development for Clarens in the Free State Province of South Africa. - Sonja Grobler; Angelo Nicolaides (African Journal of Hospitality, Tourism and Leisure, 2016)
Understanding what drives tourists is an important issue which can make or break a destination. Since tourists consume products and services and return visit/s and sustainability is desired by destinations, it is important to identify variables that influence the motivation, behaviour and satisfaction levels of tourists. The town of Clarens which is situated in the foothills of the Maluti Mountains in the Free State province of South Africa was the focus of this research study. It is labelled as the "Jewel of the Eastern Free State". Using a questionnaire survey, the researchers categorized tourists according to their demographic and socio-economic characteristics. Disconfirmation of expectations was measured using five point Likert-scales against eighteen selected variables. The findings of this study suggested that tourists were mostly satisfied with facilities, natural attractions and relaxation facilities provided by the destination. In essence, nature and adventure were experienced very positively. In contrast, tourists were disappointed with facilities such as local transport services, cleanliness and safety and security. The difference between tourist expectation and experience was diverse for different groups – for example inter alia, gender, age, international or local origin, but most of these differences were not significant. The findings presented should contribute to the development of tourism strategies which are intended to empower the town to better recognize and respond to the dynamic demand patterns of tourists and potential visitors from both the domestic and foreign market. These strategies aim towards sustainable tourism development in Clarens and the surrounding area.